What is Still Bay? Human biogeography and bifacial point variability. Issue 97 (August 2016) - Archer, Will; Pop, Cornel M.; Gunz, Philipp; McPherron, Shannon P.
Abstract: 'Still Bay' is the name given to a cultural phase within the southern African Middle Stone Age, which remains critical to our understanding of modern human behavioural evolution. Although represented in only a handful of sites, the Still Bay is widespread geographically and, at certain localities, persisted over a substantial period of time. Many studies have focused on tracing the temporal range and geographic reach of the Still Bay, as well as inferring degrees of early modern human demographic connectedness from these parameters. Variation within the Still Bay, relative to the accuracy with which it can be identified, has received considerably less attention. However, demographic models based on the spread of the Still Bay in space and time hinge on the reliability with which it can be recognized in the archaeological record. Here we document patterns of bifacial point shape and size variation in some key Still Bay assemblages, and analyse these patterns using the statistical shape analysis tools of geometric morphometrics. Morphological variation appears to be geographically structured and is driven by the spatial separation between north-eastern and south-western clusters of sites. We argue that allometric variation is labile and reflects environmentally driven differences in point reduction, whereas shape differences unrelated to size more closely reflect technological and cultural fragmentation. Our results suggest that the biogeographic structure of Middle Stone Age populations was complex during the period associated with the Still Bay, and provide little support for heightened levels of cultural interconnectedness between distantly separated groups at this time. We briefly discuss the implications of our findings for tracing classic techno-traditions in the Middle Stone Age record of southern Africa, and for inferring underpinning population dynamics from these patterns.